Frequency of Social Isolation and Homeboundness and Their Relationships with High-Level Functional Capacity in Elderly Diabetic Patients - Ida S (Dove Medical Press, 2020)
Satoshi Ida, Ryutaro Kaneko, Kanako Imataka, Kaoru Okubo, Yoshitaka Shirakura, Kentaro Azuma, Ryoko Fujiwara, Hiroka Takahashi, Kazuya Murata Department of Diabetes and Metabolism, Ise Red Cross Hospital, Ise-shi, Mie 516-8512, JapanCorrespondence: Satoshi IdaDepartment of Diabetes and Metabolism, Ise Red Cross Hospital, 1-471-2, Funae, 1-Chome, Ise-shi, Mie 516-8512, JapanTel +81 596-28-2171Fax +81 596-28-2965Email bboy98762006@yahoo.co.jpPurpose: To determine the frequency of social isolation (hereinafter, isolation) and homeboundness in elderly diabetic patients and to investigate their relationships with high-level functional capacity.Patients and Methods: Subjects were diabetic outpatients aged 65 years and older who were visiting the Japanese Red Cross Ise Hospital. Tokyo Metropolitan Institute of Gerontology Index of Competence (TMIG-IC) was used to evaluate high-level functional capacity. Isolation was defined as having less than one interaction per week with someone other than co-habiting family members. Homeboundness was defined as leaving the house less than once a day. Multiple regression analysis was performed with the TMIG-IC score as the dependent variable and isolation and homeboundness as independent variables.Results: Four hundred fifty-one patients were included in the analysis. The frequency of isolation and homeboundness affected 37% and 13.3% of men and 28.9% and 20.6% of women, respectively. The adjusted partial regression coefficient of the TMIG-IC scores of isolated, homebound, and isolated+homebound men was − 0.94 [95% confidence interval (CI), − 1.68 to − 0.21; P = 0.012], − 0.27 (95% CI, − 1.93 to 1.39; P = 0.746), and − 4.03 (95% CI, − 5.37 to − 2.68; P < 0.001) in relation to that of the non-isolated and non-homebound group as reference. In women, the respective coefficients to the reference were − 1.33 (95% CI, − 2.93 to 0.25; P = 0.099), − 0.65 (95% CI, − 2.56 to 1.26; P = 0.501), and − 3.01 (95% CI, − 4.92 to − 1.1; P = 0.002), respectively.Conclusion: The frequency of isolation was high in both female and male elderly diabetic patients. In men, there was a significant relationship between isolation and decline in high-level functional capacity. In both men and women, there was a significant relationship between isolation+homeboundness and decline in high-level functional capacity.Keywords: community-dwelling elderly, Tokyo Metropolitan Institute of Gerontology Index of Competence, TMIG-IC, diabetes in the elderly, activities of daily living